2011
DOI: 10.18097/pbmc20115704374
|View full text |Cite
|
Sign up to set email alerts
|

Poly(3-hydroxybutyrate) and biopolymer systems on the basis of this polyester

Abstract: Biodegradable biopolymers attract much attention in biology and medicine due to its wide application. The present review is designed to be a comprehensive source for research of biodegradable and biocompatible bacterial polymer, poly(3-hydroxybutyrate). This paper focuses on basic properties of biopolymer: biodegradability and biocompatibility, as well as on biopolymer systems: various materials, devices and compositions on the basis of biopolymer. Application of biopolymer systems based on poly(3-hydroxybutyr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 81 publications
0
5
0
Order By: Relevance
“…Use of biomaterials with polymeric matrices in the health field 42 is known in the literature and the promising efficacy of the biomembrane as a guide for tissue regeneration was expected. However, studies that investigated the use of norbixin such as biomaterials are recent 13 , 15 , 16 , 18 , since the most common reports still surround their application in the food industry. It is necessary to continue this research line considering the potential for application of the formulated biomaterial, as observed in this study mainly in the first days after tissue injury, necessitating the continuity of this pilot study with longer intervals of observation time, larger samples and increased inflammatory analyses, immunohistochemistry and biochemistry to know the physico-chemical interactions of this biomaterial in an isolated biological system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Use of biomaterials with polymeric matrices in the health field 42 is known in the literature and the promising efficacy of the biomembrane as a guide for tissue regeneration was expected. However, studies that investigated the use of norbixin such as biomaterials are recent 13 , 15 , 16 , 18 , since the most common reports still surround their application in the food industry. It is necessary to continue this research line considering the potential for application of the formulated biomaterial, as observed in this study mainly in the first days after tissue injury, necessitating the continuity of this pilot study with longer intervals of observation time, larger samples and increased inflammatory analyses, immunohistochemistry and biochemistry to know the physico-chemical interactions of this biomaterial in an isolated biological system.…”
Section: Discussionmentioning
confidence: 99%
“…Non-synthetic biopolymers such as polyhydroxyalkanoates, which are polymers synthesized by bacteria in the presence of renewable carbon sources, such as sugarcane, are matrix options for biomaterials, among which the polyhydroxybutyrate, C 4 H 6 O 2, can be used as a biodegradable polymer, with high potential for biocompatibility and bioreabsorption and, when implanted in living systems, do not require subsequent removal of the body and do not cause undesirable effects in the long term 10 - 13 .…”
Section: Introductionmentioning
confidence: 99%
“…In a large number of works it was shown that PHB-based materials are immunologically inert, which allows using these materials as biocompatible for different biomedical applications [ 34 , 35 , 36 , 37 ]. Composites based on PHB and various additives did not cause any inflammatory reaction accompanied by leukocyte migration [ 38 ] and they had no hemolytic effect on the red cell suspension, so were they suitable for the blood-contacting applications [ 39 ].…”
Section: Introductionmentioning
confidence: 99%
“…Biomaterials elaborated with the polyhydroxyalkanoate poly (3) hydroxybutyrate (PHB) can be used for the development of prostheses as an alternative for people with allergies to metals [7]. PHB based applications for medical devices already include membranes, plates, beads and scaffolds for tissue engineering and bone regeneration, and innovative forms of drug delivery systems [8][9][10].…”
Section: Introductionmentioning
confidence: 99%